Agricultural Economic Sustainability with Support for Training Programs, Work Skills, Community Needs for Business Actors in Kalampangan, Central Kalimantan - Harin Tiawon; Wiwin Zakiah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to evaluate the impact of training, work skills, and community needs on economic sustainability in the agricultural sector in Kalampangan, Central Kalimantan. A quantitative method was employed using a questionnaire as the data collection tool, distributed among farmers in the region. Validity and reliability tests were conducted to ensure the reliability of the research instrument. Multiple linear regression analysis using SPSS revealed that the three independent variables—training, work skills, and community needs—significantly influence economic sustainability. The findings indicate that an integrated approach combining training, skill enhancement, and addressing community needs can improve agricultural productivity and efficiency, ultimately supporting economic sustainability in Kalampangan. These results provide an empirical basis for designing more effective and sustainable programs in the agricultural sector. The study’s implications suggest that policymakers and stakeholders should prioritize holistic interventions that address both individual and community-level needs to achieve long-term economic sustainability in agriculture